Mitigasi Risiko Keterlambatan Pembangunan Jembatan Perawang di Kecamatan Tasik Putripuyu Menggunakan Simulasi Monte Carlo - Arafat, Muhammad (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study analyzes the risk of delays in the construction of the Perawang Bridge in Tasik Putripuyu District using Monte Carlo Simulation. Risk identification highlights several key factors that could cause delays, including design changes, delayed document approvals, and contractor financial issues. The Monte Carlo Simulation estimates a potential project delay of more than 30 days and a cost increase of up to 15% from the initial budget. To address these issues, the study proposes several mitigation strategies, such as improving stakeholder coordination, more effective project planning, and managing weather and safety risks. Implementing these strategies is expected to reduce the risk of delays and enhance the success of future infrastructure projects. The findings provide practical guidance for better project management and can be applied to similar infrastructure projects